Burdens on emergency responders after a terrorist attack in Berlin. (22nd December 2017) - Wesemann, U; Zimmermann, P; Mahnke, M; Butler, O; Polk, S; Willmund, G
Abstract: Background: Terrorist attacks induce various responses in emergency responders. Addressing this range of responses in individual workers is of central interest. Aims: To assess the gender- and occupation-specific effects of a terrorist attack, particularly in emergency responders. Methods: This was a pilot study. Emergency responders present during the 2016 terrorist attack at Breitscheidplatz in Berlin were asked to participate. Measures for crisis management had been previously implemented. Stress (Patient Health Questionnaire [PHQ]), quality of life (The World Health Organization Quality of Life [WHOQOL-BREF]), post-traumatic stress disorder (PTSD Checklist for DSM-5 [PCL-5]) and current psychological symptoms (Brief Symptom Inventory [BSI]) were assessed. Results: Thirty-seven subjects were included, 11 female and 26 male. The occupational groups included 16 firefighters, six police officers, five psychosocial health care personnel and nine members of aid organizations. Three months after the attack, female workers showed higher scores in stress and paranoid ideation, police officers showed higher scores in hostility and firefighters scored lower quality of life in environment and physical health. Conclusions: The mental health burden identified in this study plays an important role for emergency responders after terrorist attacks. Differences between occupational groups may be attributable to differences in tasks that responders perform during acute incidents. The presence of these differences 3 months after the incident suggests that these are at least medium-term conditions. This study may inform the development of treatments and policies and it thus recommended to develop a multi-level assessment and treatment programme that is gender- and occupation-specific.